The VISIR Open Lab Platform 5.0 - an architecture of a federation of remote laboratories - Gustavsson, Ingvar (2011)
This paper outlines a new laboratory learning infrastructure based on the VISIR (Virtual Instrument Systems in Reality) Open Lab Platform, which is an architecture for opening hands-on instructional laboratories for remote access 24/7 with preserved context. The aim is to embrace such laboratories in which telemanipulators can be used to remotely set up and/or start experiments and where the outcome can be observed remotely using instruments, video and/or audio transmission. As hands-on laboratories, VISIR ones can be used for exploring nature and for training laboratory workmanship. The current release (4.1) of the VISIR Open Lab platform can be used for opening electronics laboratories and laboratories for mechanical vibration experiments for remote access. Other subject fields will follow. So far, seven VISIR laboratories are online globally. The coming VISIR Open Lab Platform 5.0 will offer new functionality and will support a federation of VISIR laboratories.